The Analysis of the English Textbook â€œEnglish in Contextâ€ used at Junior High School - Ismiyati, Yanti; Dinata, Ridho Praja (Universitas Batanghari Jambi, 2024)
This research aimed to analyze the material completeness in the English textbook entitled â€œEnglish in Contextâ€ by the Ministry of Education and Culture. The material completeness that was expected to be found was a short interpersonal text, a short transactional text and a short functional text. The researcher used a qualitative research design and a descriptive qualitative approach to analyze the English textbook. Specifically, the researcher used a checklist in gathering the data. The data were gathered by reading the English textbook thoroughly to identify and classify the material completeness that can be found. The researcher analyzed the data by the results of the study. The result showed that â€œEnglish in Contextâ€ textbook published by the Ministry of Education and Culture provides material completeness, there are: 1) A short interpersonal text, providing introducing self and others namely introducing self, greeting, leave-taking, thanking and apologizing. 2) A short transactional text, namely daily activity, physical appearances, asking and giving information about characteristics of humans, asking and giving information about hobbies and professions, and asking and giving information about song. 3 A short functional text, namely descriptive text. The result of this research showed that this â€œBahasa Inggrisâ€ textbook fulfills the material completeness aspect.Â